2019
DOI: 10.1155/2019/3649838
|View full text |Cite
|
Sign up to set email alerts
|

Local Biological Reactions and Pseudotumor-Like Tissue Formation in relation to Metal Wear in a Murine In Vivo Model

Abstract: Metal wear debris and released ions (CoCrMo), which are widely generated in metal-on-metal bearings of hip implants, are also found in patients with metal-on-polyethylene bearings due to the mechanically assisted crevice corrosion of modular taper junctions, including head-neck and neck-stem taper interfaces. The resulting adverse reactions to metal debris and metal ions frequently lead to early arthroplasty revision surgery. National guidelines have since been published where the blood metal ion concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…[ 24 ] Although the presence of Cr, Co, and Mo is essential for certain metabolic activities in the human body, [ 25 ] the increment from a certain level is ought to be unfavorable due to potential biological inflammatory reactions and pseudotumor‐like tissue formation associated with wear phenomena. [ 24,26 ] Such corrosion of debris and its monitoring is part of ongoing studies. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 24 ] Although the presence of Cr, Co, and Mo is essential for certain metabolic activities in the human body, [ 25 ] the increment from a certain level is ought to be unfavorable due to potential biological inflammatory reactions and pseudotumor‐like tissue formation associated with wear phenomena. [ 24,26 ] Such corrosion of debris and its monitoring is part of ongoing studies. [ 27 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of metal wear debris (metal particles and ions), which is around 1/10 th of the total wear debris, have been underestimated. 4 Metal wear can cause local and systemic adverse effects (3,4,(6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies for Co28Cr6Mo implants have been conducted in vivo and in vitro and indicated that Co28Cr6Mo nanoparticles were cytotoxic and prompted cell apoptosis, and at higher dose, necrosis, with inflammatory reactions [30]. Furthermore, utilizing Co28Cr6Mo particles and ions, researchers once demonstrated that Co28Cr6Mo particles could induce more intense sterile inflammatory responses than Co28Cr6Mo ions in the synovial membrane in vivo [31]. According to some studies, wear debris-induced inflammation might be mitigated by specific pharmacological blockade of one or more of these TLRs [11,32].…”
Section: Introductionmentioning
confidence: 99%